Nutritional status and cognitive impairment in elderly population in a rural area of Thrissur district, Kerala - Ramachandran, Remya; Mundodan, Jenyz M.; Saju, C. R.; Joshy, Vidhu M. (International Journal Of Community Medicine And Public Health, 2018)
Background: The past decade has witnessed a marked increase in elderly population of India. This rapid ageing will substantially increase the number of elderly individuals, who are affected by cognitive impairment. Recent studies suggest the association between malnutrition and cognitive impairment in elderly. This study aims to describe the nutritional status and cognitive impairment in elderly population in a rural area of Thrissur district, Kerala. Methods: A community based cross-sectional study was conducted in 100 elderly residents of Adat Panchayat, Thrissur, from January to April 2016. Data was collected using a pre-tested structured questionnaire, which included socio-demographic variables, self-reported physical morbidities, mini mental state examination (MMSE) scale and mini nutritional assessment (MNA) scale. Results: The prevalence of cognitive impairment and malnutrition in elderly was noted to be 55% and 12% respectively. Factors showing significant association with MMSE score included older age groups, female gender, elderly belonging to BPL families, financial dependence, single/widowed status and sleep difficulties. The association between cognitive impairment and nutritional status was found to be statistically significant with a p value of <0.001. A moderate to strong correlation was observed between MNA score and MMSE score (r=0.623). Conclusions: There is an association between cognitive impairment and nutritional deficit. Therefore it is essential to screen elderly for nutritional status while assessing cognitive impairment.